2017
DOI: 10.1186/s12913-017-2299-8
|View full text |Cite
|
Sign up to set email alerts
|

What is the evidence for the management of patients along the pathway from the emergency department to acute admission to reduce unplanned attendance and admission? An evidence synthesis

Abstract: BackgroundGlobally, the rate of emergency hospital admissions is increasing. However, little evidence exists to inform the development of interventions to reduce unplanned Emergency Department (ED) attendances and hospital admissions. The objective of this evidence synthesis was to review the evidence for interventions, conducted during the patient’s journey through the ED or acute care setting, to manage people with an exacerbation of a medical condition to reduce unplanned emergency hospital attendance and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The existing lack of such translation-referred to as the 'know-do gap [10]"-hampers timely implementation of this knowledge. Because of the aim to deliver very short guidelines for clinical practice on one hand, and the expected low quantity and evidence-level of the literature [11,[25][26][27], we did not perform formal systematic reviews and no systematic evidencegrading, but rather used expert experience and consensus. The unmet urgent need to increase awareness, knowledge and competencies of professionals working in Geriatric Emergency Medicine validates such a pragmatic approach, but does not at all exclude that future research should further increase evidence-level and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The existing lack of such translation-referred to as the 'know-do gap [10]"-hampers timely implementation of this knowledge. Because of the aim to deliver very short guidelines for clinical practice on one hand, and the expected low quantity and evidence-level of the literature [11,[25][26][27], we did not perform formal systematic reviews and no systematic evidencegrading, but rather used expert experience and consensus. The unmet urgent need to increase awareness, knowledge and competencies of professionals working in Geriatric Emergency Medicine validates such a pragmatic approach, but does not at all exclude that future research should further increase evidence-level and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital readmission is reported as a post-discharge adverse outcome from admission and knowledge is limited on how to change the pathway for acute medical patients in order to overcome readmissions [9, 13]. Many factors have been highlighted as contributors to increased rates of patient readmission, and a common cause includes accelerated turnovers, which does not relieve the problem of overcrowded hospitals [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that use of acute medical units leads to lower admission rates and length-of-stay without increasing in-hospital mortality [9–12]. However, this type of entry includes an additional step in the trajectory for patients who require consultations with medical specialities and limited evidence exists for reducing hospital admissions along the patient pathway through the emergency department [13].…”
Section: Introductionmentioning
confidence: 99%
“…The risk-stratification of older adults presenting to the Emergency Department (ED) is useful to target interventions that reduce their risk of adverse healthcare outcomes [1,2], particularly where frailty is identified [3]. This is challenging because frail patients often present atypically [4,5], and acutely unwell hospitalised older adults may appear frailer than their baseline suggests [6], meaning that resource-intensive, evidence-based interventions such as comprehensive geriatric assessment (CGA) [7] can be difficult to apply.…”
Section: Introductionmentioning
confidence: 99%